A Systematic Literature Review on the Impact of Business Intelligence on Organization Agility - Luay Malawani; Ramón Sanguinoa; Juan Luis Tato Jiménez (Administrative Sciences)
Background: In today’s rapidly evolving business environment, organizational agility (OA) has become increasingly critical for companies to maintain competitiveness and sustainability. Business intelligence (BI) is pivotal in enabling organizational agility by providing the necessary tools and insights to navigate uncertainties and capitalize on opportunities. This study aimed to investigate the relationship between BI and organizational agility, particularly within the pharmaceutical manufacturing sector in the Middle East and North Africa (MENA) region. The systematic literature review followed Kitchenham’s guidelines, which was supplemented with a VOS analysis to visualize the interconnectedness of BI and organizational agility. The analysis revealed a direct relationship between BI and organizational agility, with the critical variables of innovation, competitive advantage, firm performance, and dynamic capabilities influencing this connection. The MENA region shows promise in contributing to this field, but further research is needed. Leveraging BI capabilities can enhance organizational agility, positioning companies for sustained success amidst uncertainty. Addressing challenges and fostering a supportive organizational culture is essential for realizing the full potential of BI-driven agility. This study makes an original and timely contribution by examining the relationship between business intelligence (BI) and organizational agility (OA) through a systematic literature review across multiple countries. The study focuses specifically on the Middle East and North Africa (MENA) region, which has received insufficient attention in previous research. Unlike previous studies that focus on isolated cases, this work combines bibliometric analysis with a structured review methodology. It provides a clear summary of how BI supports key outcomes such as innovation, dynamic capabilities, and competitive advantage